Climate Vulnerability Assessments : An Assessment of Climate Change Vulnerability, Risk, and Adaptation in Albania’s Power Sector - World Bank (World Bank, 2012)
Energy security is a key concern in Albania, which relies on hydropower for about 90 percent of its electricity production. While renewable energy resources like hydropower play a fundamental role in moving the world towards a low-carbon economy, they are also vulnerable to climatic conditions. Climate variability already affects Albania's energy production to a considerable extent, and climate change is bringing further challenges. This report summarizes work conducted in partnership with stakeholders in Albania's energy sector and other closely related sectors. It aimed to build greater understanding of the climate risks faced by the energy sector and of priority actions that could be taken to reduce vulnerabilities. The remainder of this report is set out as follows: section two describes the context for this assessment, covering the Albanian energy sector, observed and projected climatic conditions and Albania's adaptive capacity. Section three outlines the climatic vulnerabilities, risks, and opportunities facing Albania's energy sector. Section four describes the key adaptation options identified for managing climate risks to the energy sector. Section five provides the cost-benefit analysis of physical adaptation options. Section six sets out next steps for improving the climate resilience of Albania's energy sector. Finally, section seven includes references and lists of annexes and appendices.